Sensor de Deformação Baseado em FBG com Compensação de Temperatura Encapsulado em Alumínio - Bandt Neto, Martim (2018)
This work presents the development, confection, tests and results of a longitudinal deformation sensor (Strain Gage) based on Bragg gratings in standard single-mode telecommunications fiber, G-652. It uses encapsulation in aluminum body and presents temperature compensation in the same capsule by means of a second FBG for thermic monitoring. The design and structural simulation were made by Catia ™ three-dimensional modeling software, later the encapsulation was made from a 1200 H14 aluminum plate. By means of the sensor temperature characterization, the thermal sensitivity of strain sensor FGB and of the compensation temperature FBG was defined, based on the sensitivity curves of both FBGs, the temperature compensation equation was defined. A second test was carried out in the characterization in temperature, in order to define the response time of the sensor as a function of the temperature variation. Longitudinal traction tests were performed up to 8 kg (78.3 N), with steps of 1 kg (9.79 N), using standard masses. At each step wavelength variation monitoring was performed, along with the monitoring of the wavelength variation, the displacement obtained in the sensor was measured by means of a micrometer gauge. For the interrogation system, the SM125 interrogator from Micron Optics was used. By the test methodology, the results obtained shows values for measurements of deformation directly or measurement of applied force and present reasonable sensitivity and linearity as a function of applied loading/unloading.